Case report: Successful treatment of a patient with relapsed/refractory primary central nervous system lymphoma with thiotepa-based induction, autologous stem cell transplantation and maintenance - Wang, Luyao; Fan, Yili; Chen, Boxiao; Zhang, Jiawei; Yang, Luyu; Qiu, Xi; Jiang, Huawei; Li, Jinfan; Xiao, Xibin; Huang, Liansheng; Xu, Yang (Frontiers in Oncology, 2024)
Despite significant improvements in prognosis, a subset of patients with primary central nervous system lymphoma (PCNSL) remains at high risk for relapse. The treatment of relapsed and refractory (R/R) PCNSL remains a major clinical challenge. Herein, we present a 24-year-old patient with PCNSL who relapsed 4 years after initial diagnosis and subsequently became refractory to high-dose methotrexate (HD-MTX), temozolomide, whole brain radiation therapy (WBRT), ibrutinib, and lenalidomide. She received thiotepa with anti-programmed cell death protein 1 (PD-1) antibody and achieved partial remission and then underwent autologous stem cell transplantation (ASCT) with thiotepa-based conditioning. Post-transplant maintenance with thiotepa and anti-PD-1 at 3-month intervals resulted in a durable complete response (CR) in this case of R/R PCNSL. Our report highlights the important role of thiotepa in the treatment of patients with R/R PCNSL.